2021
DOI: 10.1039/d1ob00971k
|View full text |Cite
|
Sign up to set email alerts
|

A promiscuous glycosyltransferase generates poly-β-1,4-glucan derivatives that facilitate mass spectrometry-based detection of cellulolytic enzymes

Abstract: Promiscuous activity of a glycosyltransferase was exploited to polymerise glucose from UDP-glucose via the generation of β-1,4-glycosidic linkages. The biocatalyst was incorporated into biocatalytic cascades and chemo-enzymatic strategies to synthesise...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…5a). This assay also showed that human β4GalT1 (UniProt number: B2RAZ5) and bacterial lacto- N -neotetraose biosynthesis glycosyltransferase (LgtB, UniProt number: Q51116, expressed in E. coli ) 60,61 were similarly effective. The performance of all β4GalT1 variants was the same within the uncertainties of the assay, with 16% Gal conversion for bovine and human β4GalT1 enzyme and 15% for LgtB (see the ESI†).…”
Section: Resultsmentioning
confidence: 85%
“…5a). This assay also showed that human β4GalT1 (UniProt number: B2RAZ5) and bacterial lacto- N -neotetraose biosynthesis glycosyltransferase (LgtB, UniProt number: Q51116, expressed in E. coli ) 60,61 were similarly effective. The performance of all β4GalT1 variants was the same within the uncertainties of the assay, with 16% Gal conversion for bovine and human β4GalT1 enzyme and 15% for LgtB (see the ESI†).…”
Section: Resultsmentioning
confidence: 85%
“…118 Other developments involve glycoprotein labeling, 114 oxidation of Neu5Gc-containing glycans, 119 or even the labeling of polysaccharides. 120 Christophe Biot (University of Lille) then reported on the use of the Chemical Reporter Strategy to image sialylation in live cells. This approach was developed as a tool to image Congenital Disorders of Glycosylation.…”
Section: ■ Daymentioning
confidence: 99%
“…It could also be immobilized on Purolite for the oxidation of benzyl alcohols and recycled, , exploited in the chemoenzymatic synthesis of 3-deoxy-3-fluorofucose, or used in the generation of DNA-encoded libraries . Other developments involve glycoprotein labeling, oxidation of Neu5Gc-containing glycans, or even the labeling of polysaccharides …”
Section: Daymentioning
confidence: 99%
“…More recently it has been demonstrated that Neisseria meningitidis glycosyltransferase, LgtB, can be used for the in vitro polymerisation of glucose from UDP-glucose via the generation of β-1,4-glycosidic linkages, producing oligosaccharides from DP 2–10. Furthermore LgtB is permissible to biocatalytic cascades and the production of glucose oligosaccharides with tailored functionalities that can be utilised to inform on the activity of various plant cell wall degrading enzymes [ 54 ].…”
Section: Glycosyltransferasesmentioning
confidence: 99%